A wide and collimated radio jet in 3C 84. Issue Volume 14:Issue S342(2018) (May 2018) - Giovannini, Gabriele
Abstract: I report observations of 3C84 (NGC 1275), the central galaxy of the Perseus cluster, made with an interferometric array including the orbiting radio telescope of the RadioAstron mission. The data transversely resolve the edge-brightened jet in 3C84 only 0.03 mas from the core, which is ten times closer to the central engine than was possible in previous ground-based observations. To better understand physical properties of this peculiar source, I will discuss its present properties in comparison to the past and more recent evolution in the radio band of 3C 84.